2021
DOI: 10.3390/genes12040499
|View full text |Cite
|
Sign up to set email alerts
|

Cone Dystrophy Associated with a Novel Variant in the Terminal Codon of the RPGR-ORF15

Abstract: Mutations in RPGRORF15 are associated with rod-cone or cone/cone-rod dystrophy, the latter associated with mutations at the distal end. We describe the phenotype associated with a novel variant in the terminal codon of the RPGRORF15 c.3457T>A (Ter1153Lysext*38), which results in a C-terminal extension. Three male patients from two families were recruited, aged 31, 35, and 38 years. Genetic testing was performed by whole exome sequencing. Filtered variants were analysed according to the population frequency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 94 publications
2
9
0
Order By: Relevance
“…The hypoautofluorescence within the ring in DRAM2 corresponded to the RPE atrophy, which presumably followed photoreceptor loss, as has been observed in other CRD patients [30]. FAF images from follow-up visits showed the enlargement of the hyperautofluorescent rings, a clinical feature that suggests disease progression over time and that has also been reported in patients with other CRD [31,[33][34][35]. The enlarging of central hypoautofluorescence is consistent with expanding macular atrophy, and the expansion of the hyperautofluorescent ring probably reflects the disorganization of the photoreceptors during the progress of the disease [31,33].…”
Section: Fafsupporting
confidence: 65%
See 2 more Smart Citations
“…The hypoautofluorescence within the ring in DRAM2 corresponded to the RPE atrophy, which presumably followed photoreceptor loss, as has been observed in other CRD patients [30]. FAF images from follow-up visits showed the enlargement of the hyperautofluorescent rings, a clinical feature that suggests disease progression over time and that has also been reported in patients with other CRD [31,[33][34][35]. The enlarging of central hypoautofluorescence is consistent with expanding macular atrophy, and the expansion of the hyperautofluorescent ring probably reflects the disorganization of the photoreceptors during the progress of the disease [31,33].…”
Section: Fafsupporting
confidence: 65%
“…and a missense variant (p.Leu246Pro). The other six patients with relatively late disease onset (30)(31)(32)(33)(34)(35)(36)(37)(38)(39) ). We presume that certain alleles, such as p.Leu246Pro, retain some residual function of DRAM2 protein; however, a larger cohort of patients with the same genotypes and/or in vitro studies are needed to confirm this.…”
Section: Disease Onsetmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivation of the X chromosome is believed to contribute to more severe phenotype [18], however, presence of other modifying genetic factors has also been discussed [19]. According to literature, RPGR carriers are most likely to present symptoms that might be grouped in four main patterns of fundus appearance: normal or near normal pattern, a tapetal reflex, focal or patchy pigmentary retinopathy limited to a quadrant or hemisphere, and three or more quadrants of bone spicule pigmentation or atrophy [20]. Most patients complain of myopia, with 50% -72% having a refractive error of greater than −6 diopters [21].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Ttll5 −/− and Rpgr −/− mice share common features (early cone involvement and overall long-term disease progression) because both phenotypes are due to a nonfunctional RPGR ORF15 . In humans, RPGR ORF15 gene defects are observed in both CORD and RCD patients [35][36][37]. Sun et al suggested a selection bias for CORD involvement.…”
Section: Phenotype Characteristicsmentioning
confidence: 99%